Hollow-sphere iron oxides exhibiting enhanced cycling performance as lithium-ion battery anodes. Issue 77 (11th September 2019) - Ren, Qingqing; Zhang, Yaping; Liu, Chang; Han, Yi; Wang, Zhenbo; Lin, Zhan
Abstract : Hollow-sphere Fe2 O3 is synthesized as a lithium-ion battery anode. Abstract : Hollow-sphere Fe2 O3 is synthesized as a lithium-ion battery anode. Current densities for the initial material activation are important, related to electrode stability during cycling. The as-prepared anodes are able to retain 92% capacity after 1000 cycles at 1 A g −1 . The full-cells assembled with Fe2 O3 anodes and LiFePO4 cathodes exhibit good electrochemical properties.